Cost behavior in merger processes: an empirical test of the Brasil Foods company (Revista Brasileira de Contabilidade e Gestão, 2013)
The purpose of this article is to identify the reflection of the melting process in the behavior of costs in Brazil Foods Company. To achieve this goal we start from the concept of synergy and thus compares the sum of Sadia and Perdigão companies with enterprise data Brazil Foods (merged).The analyzes encompass 42 previous quarters and 16 quarters after the merger, which occurred in the second quarter of 2009. Regarding the index Cost of Goods Sold / Net Operating Revenue realizes that the fusion changed the behavior of this indicator, which, after the process has stability. However, it was in relation to the indicator Selling Expenses/Net Operating Revenue that presents the largest synergy gains due to an increase in Selling Expenses in magnitude lower than Revenue Growth. On the other hand, the index Administrative Expenses / Net Revenue has not improved with the fusion process. In contrast, the average of this ratio has increased from 13% to approximately 14.8%. Financial expenses, similarly Administrative Expenses do not present synergistic gains from the merger. When analyzing only the Net Income / Net Operating Revenue, which is a reflection of all revenues minus cost items, can realize similar situation in the two periods. Thus, it can be concluded with this study that the synergistic gains occurred in an isolated way, that is, in the indices of Cost of Goods Sold and Selling Expenses. However, in a global analysis the fusion process showed no significant impacts to businesses.
Keywords: cost behavior; fusion; Brazil Foods